Aplicación de una auditoría tributaria en la empresa Imhotepcon cía. ltda. ubicada en la provincia de Cotopaxi cantón Latacunga en el periodo del 01 de enero al 31 de diciembre del 2013 - Paredes Peñaherrera, Verónica Janeth (2015)
This research work was developed in Imhotepcon Cía. Ltda. company in Latacunga canton, in which an a Tax Audit was conducted with the issuing aim a report according to the examination results. The development research presents next methods; inductive, which one allowed knowing theoretical information that serves as an important base of the research, and the deductive method which allowed knowing the current situation of the company. Through exposed topic where business problems has been determined when it register incoming Taxes, Withholding, and IVA. Making note that the accounting assistant needs training in tax issue. However the findings do not affect legal and economically to the company, allowing a report wichone contains work findings and recommendations.